2023
DOI: 10.3390/nu15204348
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Geriatric Nutritional Risk Index for Predicting Overall Survival in Patients with Head and Neck Cancer: A Meta-Analysis

Ching-Yi Yiu,
Chien-Cheng Liu,
Jheng-Yan Wu
et al.

Abstract: Head and neck cancer (HNC) is a prevalent malignancy with a poor prognosis, necessitating the identification of prognostic biomarkers to guide management. The geriatric nutritional risk index (GNRI), calculated from serum albumin and body weight, may predict survival in patients with HNC. We performed a systematic review and meta-analysis to clarify this relationship. Databases were searched for studies examining the association between pretreatment GNRI and overall survival in patients with HNC. Ten studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The initial aim of GNRI was to evaluate the morbidity and mortality risk in elderly patients during hospitalization, with cut-off values of 98 established for identifying nutrition-related risks 8 . Subsequent studies have demonstrated that GNRI can effectively serve as a prognostic tool in patients with different types of cancers, including gastrointestinal cancer 23 , rectal cancer 24 , head and neck cancer 25 , and lung cancer 26 . However, the association between GNRI and GLIM-de ned malnutrition remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The initial aim of GNRI was to evaluate the morbidity and mortality risk in elderly patients during hospitalization, with cut-off values of 98 established for identifying nutrition-related risks 8 . Subsequent studies have demonstrated that GNRI can effectively serve as a prognostic tool in patients with different types of cancers, including gastrointestinal cancer 23 , rectal cancer 24 , head and neck cancer 25 , and lung cancer 26 . However, the association between GNRI and GLIM-de ned malnutrition remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For elderly patients with heart failure, a meta-analysis of nine studies involving 7,659 patients revealed that low GNRI was predictive of all-cause mortality (HR: 1.56) compared to high GNRI ( 62 ). In addition, low GNRI values have been associated with an increased overall mortality risk in patients with head and neck, gastrointestinal, or lung cancer, with HRs ranging from 2.39 2.84 ( 63 65 ). Considering our findings and previous research, it appears that using the GNRI as a prognostic tool in patients on hemodialysis or suffering from cancer is more beneficial than in other clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…To further assess the robustness of the finding (Fang et al, 2023) in light of heterogeneity, we conducted a prediction interval based on the raw data from the originally published metaanalysis (Fang et al, 2023). All analyses were conducted using Comprehensive Meta-Analysis (version 4; Biostat, Englewood, NJ, USA) as previously reported (Yiu et al, 2023). As shown in Figure 1, the 95% prediction interval was −1.7 to 3.73 (red line).…”
Section: Comment On Effect Of Massage Therapy On Sleep Quality In Cri...mentioning
confidence: 97%